Knowledge Worker Communications and Recipient Availability: Toward a Task Closure Explanation of Media Choice - Straub, Detmar; Karahanna, Elena (Organization Science, 1998)
Recent innovations in organizational forms, such as delayered management, empowered workers, telework, and ad hoc work groups, have created a need to ensure that communication between dispersed knowledge workers can be supported. The movement toward a less cohesive workplace suggests a need to deploy computer-based media, but it is not clear which media should be deployed and under what circumstances. Addressing such significant issues must begin with insights into why knowledge workers choose particular media for particular tasks in the first place. Prior research theorizing about media choice has focused on: (1) task, (2) medium, (3) the fit between task and medium, and (4) social environment. It has not sufficiently considered the role of the availability of the intended recipient or the interaction between recipient availability and task social presence variables which could have a significant impact on media choice. To examine the effects of these two factors, the authors conducted an initial exploratory study and a subsequent controlled factor study. In the initial study, an analysis of 1,669 hypothetical scenarios from 100 knowledge workers at a worldwide transportation company indicated that social presence (SP) theory proves to be a good predictor of media choice, as does the recipient availability construct. The analysis also suggested that the interaction between recipient availability and task social presence might be a good predictor. With a partial replication, randomized treatment design, including 1,883 scenarios from 257 workers, the controlled factor study at a large financial institution generally confirmed the study hypotheses. The authors examine rival explanations simultaneously along the dimensions of task, medium, fit between task and medium, and social environment. They propose and test a new model of media choice and suggest directions for future testing of a new “task closure” model of media choice. They conclude by offering guidelines for managers deploying electronic communications in the workplace.